Settlement Duration and Materiality: Formal Chronological Models for the Development of Barnhouse, a Grooved Ware Settlement in Orkney. (26th July 2016) - Richards, Colin; Jones, Andrew Meirion; MacSween, Ann; Sheridan, Alison; Dunbar, Elaine; Reimer, Paula; Bayliss, Alex; Griffiths, Seren; Whittle, Alasdair
Abstract : Radiocarbon dating and Bayesian chronological modelling, undertaken as part of the investigation by the Times of Their Lives project into the development of Late Neolithic settlement and pottery in Orkney, has provided precise new dating for the Grooved Ware settlement of Barnhouse, excavated in 1985–91. Previous understandings of the site and its pottery are presented. A Bayesian model based on 70 measurements on 62 samples (of which 50 samples are thought to date accurately the deposits from which they were recovered) suggests that the settlement probably began in the later 32nd century calbc (with Houses 2, 9, 3 and perhaps 5a), possibly as a planned foundation. Structure 8 – a large, monumental structure that differs in character from the houses – was probably built just after the turn of the millennium. Varied house durations and replacements are estimated. House 2 went out of use before the end of the settlement, and Structure 8 was probably the last element to be abandoned, probably during the earlier 29th century calbc . The Grooved Ware pottery from the site is characterised by small, medium-sized, and large vessels with incised and impressed decoration, including a distinctive, false-relief, wavy-line cordon motif. A considerable degree of consistency is apparent in many aspects of ceramic design and manufacture over the use-life of the settlement, the principal change being the appearance, from c. 3025–2975 calbc, of large coarse ware vessels with uneven surfaces and thick applied cordons, and of the use of applied dimpled circular pellets. The circumstances of new foundation of settlement in the western part of Mainland are discussed, as well as the maintenance and character of the site. The pottery from the site is among the earliest Grooved Ware so far dated. Its wider connections are noted, as well as the significant implications for our understanding of the timing and circumstances of the emergence of Grooved Ware, and the role of material culture in social strategies. RÉSUMÉ: Durée d'occupation et matérialité: Modèles chronologiques formels pour le développement de Barnhouse, occupation de la Céramique Cannelée à Orkney, de Colin Richards, Andrew Meirion Jones, Ann MacSween, Alison Sheridan, Elaine Dunbar, Paula Reimer, Alex Bayliss, Seren Griffiths, & Alasdair Whittle Une datation au C14, avec modélisation chronologique bayésienne, entreprise dans le cadre d'une étude du projet ' Le meilleur temps de leur vie' sur le développement d'une occupation et de poterie du néolithique final à Orkney, a fourni une nouvelle datation précise pour l'occupation de la Céramique Cannelée de Barnhouse, fouillée en 1985–91. Nous présentons les entendements antérieurs du site et de sa poterie. Un modèle Bayésien reposant sur 70 mesures sur 62 échantillons (dont 50 sont jugés dater avec précision les dépôts d'où ils ont été recouvrés) donne à penser que l'occupation commença probablement dans la dernière partie du XXXIIe siècle av.J.-C.cal (avec les Maisons 2, 9, 3 et peut-être 5a) peut-être comme fondations planifiées. La Structure 8; grande structure monumentale qui se distinguait des maisons par son caractère, fut probablement construite juste après le passage au nouveau millénaire. Diverses durées et remplacements de maisons sont évalués. La Maison 2 cessa d'être utilisée avant la fin de l'occupation et la Structure 8 fut probablement le dernier élément à être abandonné, probablement pendant la première partie du XXIXe siècle av.J.-C. La poterie de la Céramique Cannellée du site se caractérise par des récipients de petite, moyenne et grande taille avec des décorations incisées et imprimées, y compris un motif de cordon particulier, une ligne ondulée en faux- relief. Un considérable degré de consistance est apparent dans de nombreux aspects de la conception et de la fabrication de la poterie sur la durée d'utilisation/ de vie de l'occupation, le principal changement étant l'apparition, à partir d'environ 3025–2975 av. J.-C. cal. de grands récipients en poterie grossière avec des surfaces inégales et d'épais cordons appliqués, et de l'usage d'application de pastilles en creux circulaires. Les circonstances des nouvelles fondations d'occupation dans la partie ouest de l'île principale sont discutées, ainsi que l'entretien et le caractère du site. La poterie du site se situe parmi les plus anciennes Céramiques Cannelées datées à ce jour. Nous notons ses relations plus étendues, ainsi que les importantes implications pour notre compréhension de la datation et des circonstances de l'émergence de la Céramique Cannelée, et le rôle de la culture matérielle dans les stratégies sociales. ZUSSAMENFASSUNG: Siedlungsdauer und Materialität: Formale chronologische Modelle für die Entwicklung der Grooved Ware Siedlung von Barnhouse, Orkney, von Colin Richards, Andrew Meirion Jones, Ann MacSween, Alison Sheridan, Elaine Dunbar, Paula Reimer, Alex Bayliss, Seren Griffiths und Alasdair Whittle Radiokarbondatierungen und Bayesische Chronologiemodellierung, die als Teil der Untersuchungen des Times of their Lives Projekts durchgeführt wurden um die Entwicklung der spätneolithischen Siedlungsweise und Keramik von Orkney zu erfassen, erbrachte präzise neue Datierungen für die Siedlung der Grooved Ware von Barnhouse, die 1985–91 ausgegraben worden ist. Die bisherigen Vorstellungen zum Siedlungsplatz und seiner Keramik werden vorgestellt. Ein Bayesisches Modell, das auf 70 Messungen von 62 Proben basiert (von denen 50 Proben als exakt die Schichten datierend erachtet werden, aus denen sie geborgen wurden), lässt den Schluss zu, dass die Siedlung wahrscheinlich im späten 32. Jahrhundert cal.BC begann (mit den Häusern 2, 9, 3 und vielleicht 5a), möglicherweise als eine geplante Gründung. Struktur 8 – eine große, monumentale Struktur, deren Charakter sich von jenem der Häuser unterscheidet – wurde wahrscheinlich direkt nach der Jahrtausendwende erbaut. Unterschiedliche Laufzeiten und Verlagerungen von Häusern können veranschlagt werden. Haus 2 wurde noch vor dem Ende der Siedlung nicht mehr genutzt und Struktur 8 war wahrscheinlich das letzte Element, das aufgegeben wurde, wahrscheinlich während des frühen 29. Jahrhunderts cal.bc . Die Grooved Ware Keramik des Fundplatzes wird charakterisiert durch kleine, mittelgroße und große Gefäße mit geritzter und eingetiefter Verzierung, darunter auch ein auffälliges Motiv einer Wellenlinienwulst in falschem Relief. Ein bemerkenswerter Grad an Beständigkeit ist erkennbar in vielen Aspekten der Gestaltung und Herstellung der Keramik während der Nutzungsdauer der Siedlung, wobei der wichtigste Wandel zwischen ca. 3025 und 2975 cal.bc eintritt mit der Einführung von großen Grobgefäßen mit unebenen Oberflächen und dicken aufgelegten Wulsten und mit dem Anbringen von eingedrückten rundlichen Warzen. Die Umstände der Neugründung einer Siedlung im westlichen Teil von Mainland werden diskutiert und ebenso die Aufrechterhaltung und der Charakter des Fundplatzes. Die Keramik dieses Fundplatzes gehört zu der ältesten bislang datierten Grooved Ware. Ihre weiteren Beziehungen werden benannt wie auch die signifikante Bedeutung für unsere Vorstellungen vom zeitlichen Ablauf und der Umstände der Entstehung der Grooved Ware sowie von der Rolle von materieller Kultur in sozialen Strategien. RESUMEN: Duración del asentamiento y materialidad: modelos cronológicos formales para el desarrollo de Barnhouse, un asentamiento de la Grooved Ware en Las Orcadas, por Colin Richards, Andrew Meirion Jones, Ann MacSween, Alison Sheridan, Elaine Dunbar, Paula Reimer, Alex Bayliss, Seren Griffiths, y Alasdair Whittle. Las dataciones radiocarbónicas y las modelizaciones bayesianas, llevadas a cabo en el ámbito del proyecto Times of Their Lives centrado en el desarrollo de los asentamientos durante el Neolítico Final y la cerámica de Las Orcadas, han aportado una datación precisa para el asentamiento Grooved Ware de Barnhouse, excavado en los años 1985–91. Se presentan las interpretaciones previas sobre el sitio y su cerámica. El modelo bayesiano realizado con 70 dataciones realizadas a partir de 62 muestras ( de las cuales 50 muestras datan de forma precisa el contexto de procedencia) sugiere que el asentamiento probablemente comenzó a finales del siglo XXXII calbc (con las casas 2, 9, 3 y quizá la 5a), posiblemente siguiendo una fundación planificada. La estructura 8 - una estructura monumental que difiere claramente de las casas- fue probablemente construida justo después del cambio de milenio. Se estiman la duración de ocupación de las casas y su reemplazo. La casa 2 se abandonó antes del final del asentamiento, y la estructura 8 fue probablemente el último elemento en ser abandonado, posiblemente a inicios del siglo XXIX calbc . La cerámica Grooved Ware está caracterizada por un tamaño pequeño, medio y grande con decoración incisa e impresa, incluyendo como distintivo el bajorrelieve y los cordones ondulantes. Un considerable grado de consistencia es aparente en muchos aspectos del diseño cerámico y de su manufactura a lo largo de la vida del asentamiento, siendo la principal modificación la aparición, ca. 3025–2975 calbc, de grandes vasijas de manufactura grosera con superficies irregulares, gruesos cordones aplicados y el uso de botones circulares rehundidos. Se discuten las circunstancias sobre la fundación de un nuevo asentamiento al oeste en tierra firme al igual que el mantenimiento y carácter del sitio. La cerámica documentada se podría considerar entre los primeros ejemplos de Grooved Ware. Se señalan sus amplias conexiones, al igual que las significativas implicaciones que tienen para nuestra comprensión del momento de aparición de la cerámica Grooved Ware y sus particularidades, así como el papel de la cultura material en las estrategias sociales.